The Implementation of Role Playing Method in Thematic Learning to Improve Students’ Learning Activities At Elementary School - Asmayani Salimi (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2021)
The learning process can be carried out optimally if the teacher develops optimal planning. Learning without planning tends to fail because it does not reference what to do in achieving learning success. Several factors prevented educators from creating lesson plans, including; because they do not understand the lesson plan's essence, the principles of preparing the lesson plan, and the importance of the lesson plan. This study was a qualitative descriptive. In this study, data sources were primary data sources, namely data sources that directly provide data to data collectors. The primary data source in this study was a learning tool in the form of three lesson plans that have been compiled by the classroom teacher. The study procedures were flow planning, implementation, data analysis, and reporting. The data collection technique used in this study was the direct observation technique with data collection tools in observation sheets. The analysis activity began with data collection, data reduction, data presentation, and conclusion/verification. Based on the study that has been done, it can be concluded that the learning implementation plan that has been prepared by the teacher has used the role-playing method. This can be seen from the learning activities in the RPP.